5P Strategies for Management of Multiple Endocrine Neoplasia Type 2: A Paradigm of Precision Medicine - Li, Shu-Yuan; Ding, Yi-Qiang; Si, You-Liang; Ye, Mu-Jin; Xu, Chen-Ming; Qi, Xiao-Ping (Frontiers in Endocrinology, 2020)
Multiple endocrine neoplasia type 2 (MEN2) is a neuroendocrine cancer syndrome characterized by medullary thyroid carcinoma, in combination or not with pheochromocytoma, hyperparathyroidism and extra-endocrine features. MEN2 syndrome includes two clinically distinct forms subtyped as MEN2A and MEN2B. Nearly all MEN2 cases are caused by germline mutations of the RET proto-oncogene. In this review, we propose “5P” strategies for management of MEN2: prevention, prediction, personalization, , psychological support, and participation, which could effectively improve clinical outcomes of patients. Based on RET mutations, MEN2 could be prevented through prenatal diagnosis or preimplantation genetic testing. Identification of pathogenic mutations in RET can enable early diagnosis of MEN2. Combining RET mutation testing with measurement of serum calcitonin, plasma or urinary metanephrine/normetanephrine, and serum parathyroid hormone levels could allow risk stratification and accurately prediction of MEN2 progression, thus facilitating implementation of personalized precision treatments to increase disease-free survival and overall survival. Furthermore, increased awareness of MEN2 is needed, which requires participation of physicians, patients, family members and related organizations. Psychological support is also important for patients with MEN2 to promote comprehensive management of MEN2 symptoms. The “5P” strategies for management of MEN2 represent a typical clinical example of precision medicine. These strategies could effectively improve the health of MEN2 patient, and avoid adverse outcomes, including death and major morbidity, from MEN2.